Tim Gunn's fashion bible : the fascinating history of everything in your closet - Gunn, Tim (Gallery Books, 2012)
"A fascinating, meticulously researched history of Western fashion covering every topic from the history of the high heel to the origin of blue jeans. America's favorite fashion expert, Tim Gunn is also the chief creative officer of Liz Claiborne and a former faculty member and chair of fashion design at Parsons' New School for Design. From togas to Crocs, Tim Gunn presents the fascinating and exhaustive history of every item of clothing and accessory ever worn. From suits to sportswear, Gunn recounts the contributions made by revolutionary designers and surveys Western fashion, educating, enlightening, and entertaining us all!"--